Earlier and More Severe Cartilage Degeneration Occurs After Meniscal Tears in Juvenile Rabbits Compared with Adults. (March 2023) - Yan, Wenqiang; Fan, Yifei; Dai, Wenli; Cheng, Jin; Zhao, Fengyuan; Yang, Shuai; Li, Yuwan; Maimaitimin, Maihemuti; Cao, Chenxi; Shao, Zhenxing; Li, Zong; Wang, Hongde; et al.
Objective: To compare the severity of cartilage degeneration after meniscal tears between juvenile and adult rabbits. Design: This study included 20 juvenile rabbits (2 weeks after birth) and 20 adult rabbits (6 months after birth). Meniscal tears were prepared in the anterior horn of medial menisci of right knees. Rabbits were sacrificed at 1, 3, 6, and 12 weeks postoperatively. Cartilage degenerations in the medial femoral condyle and medial tibial plateau were evaluated macroscopically and histologically. The semiquantitative assessment of cartilage degeneration was graded by macroscopic Outerbridge scoring system and histological Osteoarthritis Research Society International (OARSI) scoring system. Results: In juvenile rabbits, the morphologically intact cartilage and normal extracellular matrix architecture were observed at the first week postoperatively. Mild uneven cartilage surface and toluidine blue depletion in the medial femoral condyle were observed on histological assessment at 3 weeks postoperatively. The worsened cartilage deterioration demonstrating chondral fibrillation, prominent cell death, and glycosaminoglycan (GAG) release was observed at 6 and 12 weeks postoperatively. In adult rabbits, only mild cartilage degeneration was observed in the medial femoral condyle at 12 weeks postoperatively. The outcomes of Outerbridge and OARSI scores were consistent with the aforementioned findings in juvenile and adult rabbits. Conclusions: Our study validated that earlier and more severe cartilage degenerations were observed in juvenile rabbits after meniscal tears compared with adult rabbits. Moreover, the post-tear cartilage degeneration demonstrated regional specificity corresponded to the tear position. However, caution is warranted when extrapolating results of animal models to humans.